2021
DOI: 10.1186/s40798-021-00314-w
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Cardiorespiratory and Cerebrovascular Response to Resistance Exercise

Abstract: Resistance exercise (RE) is a popular modality for the general population and athletes alike, due to the numerous benefits of regular participation. The acute response to dynamic RE is characterised by temporary and bidirectional physiological extremes, not typically seen in continuous aerobic exercise (e.g. cycling) and headlined by phasic perturbations in blood pressure that challenge cerebral blood flow (CBF) regulation. Cerebral autoregulation has been heavily scrutinised over the last decade with new data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 183 publications
(355 reference statements)
2
11
0
Order By: Relevance
“…Moreover, these beneficial physiological adaptations are specific to the modality of exercise employed, namely endurance (Tomoto et al., 2015) and resistance training (Kraemer et al., 1988). Such exercise modalities have chronic effects on the function of central and peripheral arteries (Perry & Lucas, 2021). It is thought these vascular adaptations mainly come from the patterns of MAP changes induced during exercise and the resulting shear stress across the vascular endothelium (Green et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these beneficial physiological adaptations are specific to the modality of exercise employed, namely endurance (Tomoto et al., 2015) and resistance training (Kraemer et al., 1988). Such exercise modalities have chronic effects on the function of central and peripheral arteries (Perry & Lucas, 2021). It is thought these vascular adaptations mainly come from the patterns of MAP changes induced during exercise and the resulting shear stress across the vascular endothelium (Green et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, resistance exercise shows a more varied haemodynamic profile, which by itself depends on the type of exercise performed (i.e., static vs. dynamic). For more details on the cardiovascular and cerebrovascular responses to acute resistance exercise, we refer the reader to Perry and Lucas (2021). Overall, the MAP profile from resistance exercise has been shown to lower arterial compliance in central arteries (Miyachi et al, 2004).…”
mentioning
confidence: 99%
“…Thus, the Valsalva maneuver may play a role of protecting the cerebral vasculature against an acute increase in perfusion pressure (Haykowsky et al 2003). Indeed, resistance exercise with a Valsalva maneuver did not change the CBF, despite a larger elevation in ABP at Valsalva phase I and IIb (Pott et al 2003;Perry et al 2020;Perry and Lucas 2021). These findings suggest that the response to breathhold is different from that of the Valsalva maneuver.…”
Section: Introductionmentioning
confidence: 92%
“…In regard to respiration during exercise, the previous studies (Linsenbardt et al 1992;Pott et al 2003;Perry et al 2020;Perry and Lucas 2021) have investigated the effect of the Valsalva maneuver on ABP and cerebral blood flow (CBF), because it is a type of breath-hold that sometimes occurs during resistance exercise (MacDougall et al 1992). The Valsalva maneuver causes an increase in intracranial pressure that decreases CBF (Haykowsky et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Acute aerobic, mild-to-moderate intensity exercise could increase CBF, whereas high-intensity exercise (above anaerobic threshold) leads to CBF decline (Smith and Ainslie, 2017 ). Moreover, a study evaluating acute resistant/strength exercise effects has demonstrated a reduction in CBF (Perry and Lucas, 2021 ). With regard to chronic exercise, the studies conducted thus far suggest an improvement in CBF as well as cerebrovascular reactivity (Ainslie et al, 2008 ; Murrell et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%